Secondary geography for Brunei Darussalam - James, Gethin (Macmillan, 1991)
"Book 1 provides a solid foundation of geographical ideas and skills related to the local environment of Brunei Darussalam. It then goes on to examine the country's links with the rest of the world. Local map extracts are used to consolidate map reading skills."